Deep eutectic solvent catalyzed Friedel–Crafts alkylation of electron-rich arenes with aldehydes1. Issue 73 (9th August 2015) - Wang, Ailing; Xing, Pengfei; Zheng, Xueliang; Cao, Hongyu; Yang, Guang; Zheng, Xuefang
<x xml:space="preserve">Abstract</x> In this study, six deep eutectic solvents were synthesized. Research shows that [ChCl][ZnCl2]2 can be used for catalyzing F–C alkylations of electron-rich arenes with aldehydes successfully. After five cycles, the yields remain about 89–94%.